Pemodelan 3D Tekla Structure Pada Konstruksi Baja Project Warehouse Finish Good Dalam Proses BIM (Building Information Modeling) - prasdiansyah, David; Ronny Durrotun Nasihien; Julistyana Tistogondo (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
The construction of the warehouse finish good uses steel construction, for accuracy and acceleration in fabrication of steel requires accuracy in the section of steel pieces, connections, accessories and bolt hole point spacing. Based on reviews in the field, all project parties need 3d results and building planning, which can estimate problems and determine what methods will be used in the implementation in the field. In this Warehouse Finish Good project, development planning uses 2 BIM-based software for steel structures using the Tekla Structure program and for planning earthquake-resistant steel buildings using the SAP 2000 program. The purpose of this research is to study BIM (Building Information Modeling) based technology with the Tekla structure implementation method, the results obtained from the implementation can be 3d modeling and can find out the material requirements that will be used where BIM (Building Information Modeling) is very useful for the field implementation process and can also be a discussion material for all project-related teams to determine the work methods to be used.